Toxoplasma Oocyst Contamination in Water Sources in Goat-Sheep Farming In Sidoarjo District - Mufa, Ramy Inas Mahirah; Eka Pramyrtha Hestianah; Lucia Tri Suwanti; Hani Plumeriastuti; Widya Paramita Lokapirnasari; Tony Hartono; Rina Vitriasari; Retno Yuli; Galaxy Guardian; Heni Puspitasari; Mufasirin (Universitas Airlangga, 2025)
Toxoplasmosis is one of the zoonotic diseases caused by the protozoa Toxoplasma gondii. The disease infects warm-blooded animals including humans. The purpose of this study was to determine the contamination of Toxoplasma oocysts in water sources in goat-sheep farms in Sidoarjo Regency. A total of 63 water samples were used for the study. Water samples were taken from 5 sub-districts that have many goat-sheep farms, each sub-district has 2 villages, with each village having 6-7 samples. The examination used the floating method and was examined under a microscope with a magnification of 400x. The results of the examination found 21 samples of Toxoplasma gondii oocysts or 33.33% (21/63). The morphology of T.gondii oocysts is round, ovoid or ellipsoid with sizes varying between 8.02 - 12.72 micrometers. Preventive measures are needed by treating water before giving it to livestock.